PERTANIAN BERORIENTASI KEWIRAUSAHAAN: FAKTOR PEMICU GENERASI MUDA MEMULAI BISNIS PERTANIAN - Gema Wibawa Mukti; Dini Rochdiani; Iwan Setiawan (Universitas Galuh, 2022)
Entrepreneurship is an important issue in Indonesia because it is considered to be able to overcome various development problems, such as creating new jobs and supporting the realization of economic growth. The purpose of this study is to determine the factors that encourage farmers to start new business activities, both farming and non-agricultural businesses that can be a source of income for them. The study uses several approaches/perspectives to explore the factors that trigger young farmers to start new business activities, namely 1) rural sociology perspective in agricultural entrepreneurship, 2) opportunity perspective in agricultural entrepreneurship and 3) resource perspective in agricultural entrepreneurship. Entrepreneurial farmers who are always looking for new business ideas, see and capture new opportunities and are able to utilize the resources they have are indispensable for agricultural development in rural areas. Farmers who have entrepreneurial characteristics are actors who can be expected to develop the economy of rural communities. In essence, all types of farmers described in this study can contribute to the development of the agricultural sector, create new jobs, new economic activities, discover unique resources and maintain the existence of agriculture in Indonesia as an agricultural country.